Hybrid Precoding Technique With Iterative Algorithm for MIMO-OFDM System - Seulgi Lee; Won-Seok Lee; Jae-Hyun Ro; Young-Hwan You; Hyoung-Kyu Song (IEEE Access)
This paper proposes a hybrid precoding technique based on multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) system to improve bit error rate (BER) performance in hybrid beamforming system. The conventional hybrid beamforming system cannot outperform the performance of full-digital beamforming system in OFDM. In the proposed algorithm, the analog precoding matrices are designed by iterative algorithm and one proper analog precoding matrix with the highest power of hybrid precoder is selected to achieve the highest performance. According to the number of analog precoding matrices, the diversity gain is increased and the performance is improved. The simulation results show that the BER performance and average sum rate for the proposed scheme are higher than the conventional hybrid beamforming system.